Therapeutic collaboration and resistance: describing the nature and quality of the therapeutic relationship within ambivalence events using the therapeutic collaboration coding system - Ribeiro, A. P. (2014)
We understand ambivalence as a cyclical movement between two opposing parts of the self. The emergence of a novel part produces an innovative moment, challenging the current maladaptive self-narrative. However, the novel part is subsequently attenuated by a return to the maladaptive self-narrative. This study focused on the analysis of the therapeutic collaboration in episodes in which a relatively poor-outcome client in narrative therapy expressed ambivalence. Method: For our analysis we used the Therapeutic Collaboration Coding System, developed to assess whether and how the therapeutic dyad is working within the therapeutic zone of proximal development (TZPD). Results: Results showed that when the therapist challenged the client after the emergence of ambivalence, the client tended to invalidate (reject or ignore) the therapist’s intervention. Conclusions: This suggests that in such ambivalence episodes the therapist did not match the client’s developmental level, and by working outside the TZPD unintentionally contributed to the maintaining the client’s ambivalence.